Gambaran Perilaku Jajan dan Status Gizi Pada Remaja di SMP Negeri 1 Mamuju - Nurbaya, Nurbaya; Jamilah S, Jamilah S; Najdah, Najdah; Yudianti, Yudianti; Irwan, Zaki; Al-Fath, Muhammad Dzulifsal (Bomba: Jurnal Pembangunan Daerah, 2025)
Snacking habits among school-aged adolescents can influence nutrient intake and affect their nutritional status, particularly in school environments where ready-to-eat foods high in sugar, salt, and fat are widely available. This study aimed to describe the snacking behavior and nutritional status of students at SMP Negeri 1 Mamuju, Mamuju Regency. A quantitative descriptive design was employed with a sample of 192 students from grades VII and VIII, selected using proportional random sampling based on the Slovin formula. Data were collected through structured questionnaires assessing snacking behavior, frequency of snack consumption, attention to nutritional content, and anthropometric measurements using a digital scale and microtoise to determine nutritional status via the BMI-for-age index. The results showed that most respondents had moderate snacking behavior (90.6%), while good and poor behaviors were reported in 7.3% and 2.1% of students, respectively. The majority consumed snacks at a moderate frequency (66.7%) and consumed colored snacks (75.0%), yet only 28.6% paid attention to snack nutritional content. Most students had a normal nutritional status (90.6%), with undernutrition (3.1%), overweight (5.7%), and obesity (0.5%) reported in smaller proportions. Chi-square analysis revealed no significant association between snacking behavior or snacking frequency and nutritional status (p>0.05). These findings highlight the need for nutrition education programs and healthy canteen initiatives in schools to improve healthy snacking behaviors while maintaining optimal nutritional status